Conditional cash transfers, school progression and academic achievement in Jamaica - Diether W. Beuermann; Andrea Ramos Bonilla; Marco Stampini (Inter-American Development Bank (IDB), 2025)
Covering the full population of applicants to the Jamaican Conditional Cash Transfer Program (PATH), we explore whether receiving PATH during childhood causally affects school progression and academic performance at the primary, secondary and tertiary levels. To uncover causal associations, we exploit exogenous variation arising from the PATH eligibility criteria within a regression discontinuity design. We find that for both, boys and girls, PATH significantly increases the likelihood of completing primary and secondary school. Furthermore, among boys, PATH increased the likelihood of pursuing tertiary studies. However, conditional on primary school completion, PATH had no effects on academic performance at any educational level.
Keywords: H52; H75; I21; I26; I28; I38; 330; academic performance; conditional cash transfers; Jamaica